2019
DOI: 10.1002/chem.201903145
|View full text |Cite
|
Sign up to set email alerts
|

A Multi‐crosslinking Nanocapsule‐Based Serial‐Stimuli‐Responsive Leakage‐Free Drug‐Delivery System In Vitro

Abstract: As some stimuli utilized in conventional drug delivery systems can also be found in normal cells, it is inevitable that encapsulated drugs escape from carriers into normal cells. Based on mutual interactions among proteins, polyphenol compounds, and metal ions, we developed a serial‐stimuli‐responsive drug delivery system. With multi‐crosslinking structure, nanocapsules can maintain the integrity of the framework, even with a certain amount of stimuli present, and eventually reach tumor cells to initiate apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…This result suggested that after the NPs reached the tumor region, the encapsulated DTX can be released quickly since the tumor microenvironment is known to be mildly acidic . In addition, as shown in Figure i, for the DTX-loaded Zein/CSP NPs without GTP/Fe III coating, the DTX releases were almost identical under different pH conditions, which demonstrated that such pH-responsiveness was mainly due to the presence of the GTP/Fe III network, since there were references reporting that the coordination complex tends to disassemble under acidic environment …”
Section: Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This result suggested that after the NPs reached the tumor region, the encapsulated DTX can be released quickly since the tumor microenvironment is known to be mildly acidic . In addition, as shown in Figure i, for the DTX-loaded Zein/CSP NPs without GTP/Fe III coating, the DTX releases were almost identical under different pH conditions, which demonstrated that such pH-responsiveness was mainly due to the presence of the GTP/Fe III network, since there were references reporting that the coordination complex tends to disassemble under acidic environment …”
Section: Results and Discussionmentioning
confidence: 76%
“…41 In addition, as shown in Figure 1i, for the DTX-loaded Zein/CSP NPs without GTP/Fe III coating, the DTX releases were almost identical under different pH conditions, which demonstrated that such pH-responsiveness was mainly due to the presence of the GTP/Fe III network, since there were references reporting that the coordination complex tends to disassemble under acidic environment. 42 In Vitro Photothermal Effect. As a parameter to reflect the photothermal properties of materials, the photothermal conversion efficiency of NPs was computed using the methods in previous references.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The addition of gallic acid (GA), a polyphenolic compound that can be found in various natural foods and fruits, together with doxorubicin (DOX) in multi-crosslinking nanocapsules increased the cytotoxic effect for HepG2 liver cancer cells [ 161 ]. Results indicated that the systems could minimize side effects and optimize cancer therapeutic efficacy.…”
Section: Application Of Nanotechnology Improving the Efficiency Of Po...mentioning
confidence: 99%